OCP Oracle Certified Professional Java SE 17 guide : exam 1z0-829 - Selikoff, Scott (John Wiley & Sons, Inc, 2022)
An effective and practical study aid to the new OCP Java SE 17 Developer certification exam In the OCP Oracle Certified Professional Java SE 17 Developer Study Guide: Exam 1Z0-829, you'll find accessible and essential test prep material for the in-demand and practical OCP Java SE 17 Developer certification. Providing comprehensive coverage of all OCP Java SE 17 exam objectives and competencies, the Study Guide offers you access to all the skills and knowledge you'll need to succeed on the test and in the field as a new or experienced Java developer. This book provides material on records, sealed classes, text blocks, dates, streams, controlling program flow, using the Java object-oriented approach, handling exceptions, working with arrays and collections, and more. You'll also get: Intuitively organized information that aligns with the competencies tested on the exam and those required by real-world Java developers Opportunities to practice and develop skills that remain in high demand in the IT industry Access to the Sybex online learning center, with chapter review questions, full-length practice exams, hundreds of electronic flashcards, and a glossary of key terms Perfect for anyone prepping for the brand-new OCP Java SE 17 credential, OCP Oracle Certified Professional Java SE 17 Developer Study Guide: Exam 1Z0-829 is also a can't-miss reference for practicing and aspiring Java developers seeking to learn or reinforce their foundational skills in Java programming and improve their performance on the job.